TRACER STUDY AND LABOUR MARKET SIGNAL UNTUK LULUSAN DIII ANALIS KESEHATAN POLITEKNIK KESEHATAN KEMENKES JAKARTA III - Estu Lestari Lestari; Retno Martini Widhyasih; Warida Warida Warida (Poltekkes Kemenkes Jakarta III, 2014)
Public demands into a high quality of health examination with right, accurate and appropriate are increased. Hence, it is responsibility of health professional to provide better service. However, the number of health analyst workers called laboratorian have various diverse of educational background. In respon to providing high quality analysts, Polytechnic of Health Ministry of Health Jakarta III intends to identify its graduation who work in health services in Jakarta and surrounding areas. This study aims to evaluate the progress of Program D III at Health Analyst department as well as its development; to assess the need of user about health analysts education level; and to improve the performance of Health Analyst department. The study is designed as cross-sectional with the use of descriptive research / survey type. The target of population were the entire graduated of Health Analyst department. Data collection was conducted in the area of Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek) among alumni who work in hospital laboratories and 9 (nine) Clinics and Health Centers. Total number samples participated is 94 alumni. All data collected then was analyzed using SPSS. Learning experience in laboratory is the most important for alumni competence in the workplace, followed by learning experience in a community and hospital internships. It means there is association between education and the job attained. Professional certification is more important than academic achievement (IP), and participant expecting DIII program development into Bachelor level.